Does the New Revised Code of Corporate Governance Impede Board Diversity? Evidence from Indonesia - Desi Ilona; Shamharir Abidin; Nurwati A Ahmad-Zaluki; Zaitul zaitul (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study explores the effect of Indonesia's good corporate governance code on board diversity: ethnicity, nationality, gender, qualification, experience, composition, and multiple directorship diversity. The revised corporate governance code provides guidelines for better corporate governance practices. Therefore, board attributes such as diversity are among the best corporate governance practices. Two hundred and three of Indonesia's listed companies (1,421 firm years) are research objects. The data was collected from company annual reports and other internet sources. The data was analyzed using a pair sample t-test and distribution frequency. Based on the pair sample t-test, Oversight board ethnicity diversity, nationality diversity, gender diversity, and board composition significantly differ between pre- and post-revised codes. In addition, management board nationality diversity and gender diversity are also differences between the pre-and post-revised code. In most cases, updating code improves diversity, except for the Oversight Board's ethnic diversity. This study also provides the detailed average number and percentage of board diversity pre- and post-the-updated code of good corporate governance. This study implies that the revised code of good corporate governance increases the board diversity of Indonesian-listed companies. Since the last revised code was released in 2006, a new updated code of good corporate governance has been demanded.